"Tipo de maltrato y agresividad en adolescentes de la I.E. Marcial Acharán y Smith, Trujillo - 2008" - Calle Morales, Veronica de Jesús (2009)
This research study is quantitative descriptive correlation was conducted during the months of August, 2007 to September, 2008, with the purpose of determining the relationship between the types of abuse (physical, psychological and sexual) and the aggressiveness of adolescents Marcial Acharan and Smith. The sample was made up of 288 teenagers between the ages of 12 to 17 years for both sexes and attending the first to the fifth year of secondary education in the school "Marcial Acharan and Smith." For data collection was used 02 instruments: Format semiestructurada Types of abuse on the scale and aggressiveness of AGA. The data were processed following a pattern and statistical manual tabulation by the Test of Independence criteria Chi square, reaching the following conclusions: The 45.5 percent (131) of adolescents surveyed had suffered psychological abuse and 1.4 percent (4) presented physical abuse, psychological and sexual; 59.0 percent (170) presenting low aggressiveness and 1.4 percent (4) high aggressiveness and therefore in this study did not find significant relationship between variables Types of abuse (physical, psychological and sexual) and aggressiveness.